SISTEM INFORMASI WARTA DESA (SIWADA) DENGAN MENGGUNAKAN SMS GATEWAY PADA DESA KLAMBIR LIMA KEBUN - Perwitasari, Ika Devi; Hendrawan, Jodi; Putri, Nadya Andhika (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
The Village News Information System or SIWADA is an information system designed for use in Klambir Lima Kebun Village. SIWADA is used to spread important news and announcements in the village. The system is built based on a website by utilizing SMS Gateway technology. News or announcements from the village are delivered via broadcast messages to all resident numbers registered in the system. Announcements and broadcast news can be in the form of information such as the Covid-19 vaccine schedule, village meeting schedule, information on activities that involve residents and much other information that needs to be conveyed by the village to its residents. In this way, information will reach each villager more quickly. It also increases the truth of the information received by residents. The SIWADA development process is carried out using the Prototype model and UML methods as a design tool.